Status of Teaching and Learning Mathematics for Students with Visual Impairment Studying in Inclusive and Special School Settings - Sharma, Vijay Shankar (JOURNAL OF INDIAN EDUCATION, 2022)
Mathematics is important for students with visual impairment just like for nondisabled students. Learning of mathematics by visually impaired students is generally considered tough as some of the areas in Mathematics demand vision. Several research studies reveal that visually impaired children can also learn mathematics when they are taught in an appropriate manner. The present paper focuses on a study which was conducted to find out the available provisions of learning mathematics by visually impaired children who are studying mathematics in inclusive as well as special school settings. The paper will put some light on various aspects related to availability of resources, trained human resources, interest and aptitude of visually impaired students towards learning mathematics. The paper also ponders upon the provisions made for making the learning of mathematics accessible for students with visual impairment by various education boards of northern part of India. The paper will also provide a structured format of teaching mathematics to visually impaired students. The paper will sum up by justifying the importance of Mathematics learning for children with vision loss.